2020
DOI: 10.5858/arpa.2020-0284-ra
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Spread of Antimicrobial Resistance, Bacterial and Fungal Threats to Coronavirus Infectious Disease 2019 (COVID-19) Survival, and Point-of-Care Solutions

Abstract: Context. Point-of-care testing (POCT) is inherently spatial, that is, performed where needed, and intrinsically temporal, because it accelerates decision making. POCT efficiency and effectiveness have the potential to facilitate antimicrobial resistance (AMR) detection, decrease risks of co-infections for critically ill COVID-19 patients, and improve the cost-effectiveness of healthcare. Objectives. To assess AMR identification using POCT, describe the United States AMR Diagnostic Challenge, and improve globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…Several antimicrobial drugs have lost their effectiveness in recent years and are no longer suitable for treating infections caused by multidrug‐resistant bacteria. In addition, the heavy use of antibiotics is becoming even more critical in the Coronavirus (COVID‐19) pandemic (Kost, 2021; Razzaque, 2020), which could further increase this phenomenon. Faced with this resurgence, it is necessary to explore new therapeutic approaches such as QQ as an innovative strategy to counter the real scourge of antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Several antimicrobial drugs have lost their effectiveness in recent years and are no longer suitable for treating infections caused by multidrug‐resistant bacteria. In addition, the heavy use of antibiotics is becoming even more critical in the Coronavirus (COVID‐19) pandemic (Kost, 2021; Razzaque, 2020), which could further increase this phenomenon. Faced with this resurgence, it is necessary to explore new therapeutic approaches such as QQ as an innovative strategy to counter the real scourge of antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Societies also need significant resources and dedicated funding to deal with emerging and re-emerging infectious diseases focusing on its future recurring possibilities, prevention and management [ 157 ]. There should be incentives given to people for early reporting [ 158 ] followed by developing strategies to prevent antimicrobial resistance [ 159 , 160 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Rawson et al (2020) found that 72% of COVID-19 patients received antibiotics during hospital admission, while less than 10% experienced bacterial/fungal coinfections. Thus, some studies warn that a marked increase in antibiotic-resistant bacteria should be expected (Miranda et al, 2020) and this will cause millions of human deaths annually by 2050 (Kost, 2021).…”
Section: Impacts Of Cecs On Ecosystems and Human Healthmentioning
confidence: 99%